TERAPAN MCRNG SEBAGAI GENERATOR ACAK UNTUK GAME - Usman Nurhasan; Bagus Purnomo (Jurnal Saintekom)
Most game s are used as a means of entertainment, but can also function as a means of training, education and simulation. In the field of education, educational game s can be applied by adopting educational materials to be informed in an interesting way to users. To provide a challenge to the user, the concept of level and scoring is applied in the game . The type of game  made is a quiz-based educational game . Elements of educational game s made in the form of text, images, sounds and videos regarding knowledge about the classification of vertebrate and invertebrate animals. The data and answers used in the quiz are also displayed in a random way. The randomization process uses a random generator that applies the concept of Multiplicative Congruential Random Number Generator (CRNG). The use of this generator is intended so that users get different questions and answer compositions at each level. This is so that the user does not get bored quickly and the game  becomes more interesting to play. So that the user indirectly conducts learning activities because the information conveyed is in the form of knowledge that is packaged in the form of a game.